Efecto de dos tipos de compost en el rendimiento de lechuga arrepollada (Lactuca sativa L.) en el distrito de Marcabalito, provincia de Sánchez Carrión - Castillo Pastor, Wester Ademir (2019)
Domestic and agricultural organic waste, generated in the district of Marcabal, is dumped and deposited in grazing areas, causing pollution by bad odors and attracting vectors transmitting diseases. To solve this problem, this research was carried out to make compost from these residues, with the aim of evaluating their efficiency by applying as fertilizer to the cultivation of repealed lettuce (Lactuca sativa L.) Great Lakes 659 variety, quantifying the weight obtained, as well as morphological characteristics such as the height and diameter of the plant. A total of 16 small plots or mastics were planned for an area of 2m2 each, divided into 4 blocks. In addition, holes of 1 m3 of capacity were excavated to prepare two types of compost: one of mainly homemade organic waste, called T1 and another of mainly domestic animal manure, called T2. Subsequently, a mixture was made in equal parts of both compost, calling it T3. With the T3 treatment, an average maximum weight of lettuce was obtained of 209.89 grams compared to the T1 and T2 treatment which obtained 192.09 and 160.03 grams respectively. With regard to the evaluation of the treatments and their influence on the lettuce height, with the treatment T3 a maximum average height of 19.4 cm was obtained, in front of the other two treatments T1 and T2 which a produced in lettuce heights of 18.8 and 16.3 respectively. The average maximum diameter of the repealed lettuce obtained with the compost obtained from the mixture of T1 and T2, called T3, was 27.0 cm in contrast to the treatments T1 and T2, that produced average diameters of 24 and 24.9 cm. Based on these experimental results it was concluded that the effect of the mixture of two compost, recorded as T3, was the most effective in improving the yield of the repealed lettuce (Lactuca sativa L.)